Impact of Covid-19 on Ear Nose and Oral Health during Pandemic - Srividhya Srinivasan; K. Saraswathi Gopal; P. Mahesh Kumar; V. Poongodi; R. Anitha (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
The Severe Acute Respiratory Syndrome (SARS) coronavirus-2 is a novel coronavirus belonging to the family Coronaviridae originating in Wuhan, China has created an impact across the globe. The SARS-CoV-2, which started initially as a severe pneumonia outbreak in China, has now quickly spread all throughout the globe, COVID-19 has affected a large number of people being reported in approximately 200 countries and territories. The disease has been declared a pandemic by the WHO on March 11, 2020. In this review, an update on virology, pathophysiology, and clinical presentation with a detailed update on oral manifestations. The main suspected mechanism is invasion of the olfactory receptors centrally or damage of the olfactory epithelium which leads to post olfactory loss. Anosmia is usually associated with frontal headache.